Long-term facial artery catheter implantation for serial arterial blood sampling and invasive arterial blood pressure measurement in horses - Martins Dias, Deborah Penteado [UNESP]; Teixeira, Luisa Gouvea [UNESP]; Canola, Paulo Alescio [UNESP]; Albernaz, Raquel Mincarelli [UNESP]; Marques, Jose Antonio [UNESP]; de Lacerda Neto, Jose Correa [UNESP] (Elsevier B.V., 2012)
The purpose of this investigation was to evaluate surgical catheter implantation in the facial artery of horses and the long-term maintenance of such arteries using heparin and ascorbic acid as filling solution. Nine horses were implanted with a polyurethane catheter. The catheters were flushed with a heparin/ascorbic acid solution every 8 h and remained patent for 25 days. Arterial blood samples were collected twice a day, and one exercise test that included serial blood samples and arterial pressure recordings was performed on a treadmill. Polyurethane catheters surgically implanted in the facial artery can be kept patent by filling with a heparin/ascorbic acid solution and provide convenient invasive arterial access in horses which is suitable for use for serial blood sampling and blood pressure recordings, even during exercise on treadmill. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Arterial blood pressure; Arterial blood sampling; Catheter; Exercise; Horse